TANGGAPAN TAMU TERHADAP KUALITAS PELAYANAN PRAMUSAJI DI RESTORAN ARYADUTA HOTEL PEKANBARU - Yulni, Mila Ade; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this research to know The quality of the waiter service and the waiter's efforts in improving the quality of services consisting of five dimensions , namely Tangibless, Emphaty, responsivnes, Reliability, assurance. The research method used in this research is a descriptive quantitative method. The population of this research is the guests who eat and drink at Aryaduta Hotel Pekanbaru's restaurant. Samples in this study used an accidental sampling sample. Data collection in this study used observations, interviews, questionnaire, Literature Studies, and documentation studies, using the Instrument measurement scale of Likert scale. The data analysis techniques used are descriptive statistics. Based on the research conducted at Aryaduta Hotel Pekanbaru, the result of data processing shows the level of the waiter's service both on the dimensions tangibless, Emphaty, responsivnes, Reliability and assurance .